Lapo as a Communicative Space: Constructing Batak Identity and Cultural Memory Among Migrants in Greater Jakarta - Evvy Silalahi; Simon Simon (Jurnal Sosial Teknologi, 2026)
This study analyzes the role of Lapo in the Greater Jakarta (Jabodetabek) area as a space for communication and cultural reproduction for the Batak ethnic community in an urban context. In a metropolitan environment characterized by high mobility and ethnic diversity, ethnic culinary spaces serve not only as places of food consumption but also as space for constructing and maintaining social identity. Using a qualitative approach, data were collected through in-depth interviews with three informants, complemented by field observations and document analysis. Thematic analysis was employed for data interpretation. The findings reveal three main dimensions of Lapo’s role: First, it serves as a space for the construction and reaffirmation of Batak identity through consumption practices and social interactions among diaspora members. Second, Batak identity is represented through cultural signifiers such as traditional food, Batak music, and spatial atmosphere, balancing ethnic identity and urban professionalism. Third, Lapo activates collective memory and transmits identity across generations through shared sensory experiences and communal dining. This study concludes that Lapo is not just a culinary venue but a social space that produces and reproduces Batak cultural identity in an urban environment, contributing to cultural communication and social construction studies.